1988
DOI: 10.1007/bf01794786
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders: The cultural dimension

Abstract: "As periods of cultural change inevitably carry with them a greater degree of heterogeneity, in the history of any culture or subculture, periods will be found in which adequate social forms for expression of strain or tension will be lacking and the individual will be forced back upon his own body for symbolic expression."Margaret Mead 1947 Summary. The role of socio-cultural factors in the pathogenesis of eating disorders, anorexia nervosa and bulimia has been the object of recent interest. The phenomena,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 24 publications
2
49
1
Order By: Relevance
“…Anorexia nervosa outside westernized societies is a rare occurrence. Nasser (1988) reviewed the literature on the prevalence of eating disorders and the role of sociocultural factors in their pathogenesis. In the Sudan, anorexia nervosa is considered a rare symptom of hysteria (El-Sarrag, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorexia nervosa outside westernized societies is a rare occurrence. Nasser (1988) reviewed the literature on the prevalence of eating disorders and the role of sociocultural factors in their pathogenesis. In the Sudan, anorexia nervosa is considered a rare symptom of hysteria (El-Sarrag, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…These pressures may not occur in nonwesternized societies, and cross-cultural variations regarding body weight and feminine beauty have been recognized. In Arab culture, thinness has been regarded as socially undesirable, whereas plumpness is regarded as a symbol of fertility and womanhood (Nasser, 1988). Africans have the custom of sending their young girls to fattening houses to make them ready for marriage (El-Sarrag, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural change in non-Western countries involving identification with Western norms of shape and body weight is consistently correlated with an increase in weight consciousness and the risk of developing eating disorders. [3][4][5][6] As a unique multicultural society encompassing various ethnic and religious groups and immigrants from many different countries, Israel is coping with the same issues. In the last three decades, large numbers of Israeli-Jewish adolescents in nonclinical settings have been found to have abnormal eating attitudes and weight concerns 7-9 (Latzer et al Comparative study of eating related attitudes and psychological traits between Israeli Arab and Jewish schoolgirls.…”
Section: Introductionmentioning
confidence: 99%
“…15 Thus, it is not surprising that low rates of ED have been reported among Arab populations. 3,4,[16][17][18] A few studies examining the prevalence of eating disorders have been conducted in Arab cultures, including two studies that reported cases of BN in Pakistan. 19,20 In another study on female Arab students in London and Cairo Universities, Nasser 18 found that 12% of the participants in the London group met Russell's 21 criteria for BN, whereas none of the Cairo group reported bulimic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…She suggested that rapid acculturation to the thin ideal of beauty in the US or disruption of traditional family roles might be involved. Around this same time, Nasser (1988) argued that anorexia and bulimia should be considered "culture-bound" syndromes because they appeared to be linked to "…a recent change in Western values in relation to female shape with more emphasis on thinness…" (p. 574).…”
mentioning
confidence: 99%